Application of fuzzy TOPSIS in selecting the major factor influencing Malaysians' choice of University (IPTA or IPTS) / Nur Syuhada Muhammat Pazil ... [et al.] - Muhammat Pazil, Nur Syuhada; Mahmud, Norwaziah; Jamaluddin, Siti Hafawati; Shakiren, Saidatul Shareen (UiTM Cawangan Perlis, 2018)
Currently there are about 500 institutions throughout Malaysia which offer tertiary education level. They consist of public and private colleges. However, this variety will lead to confusion among the Malaysians in order to choose the right places to further their studies. The aim of this study is to select and rank the significant factor which influences the selection of university between IPTA and IPTS. By approaching the main objective, the sub-objective; to determine the most preferred university based on the associated factor can also be examined. Fuzzy TOPSIS (Fuzzy Technique for Order Preference by Similarity to Ideal Solution) is one of the best methods to assess this kind of multi-criteria decision-making problem. The alternative of this research will be the factors influencing Malaysians' choice of universities which are affiliation, course offered, cost of education and reputation. While the criteria will be IPTA and IPTS. The data was collected by interviewing experts in both fields; public and private sectors. The result referred by the value of closeness coefficient of each alternative is determined in order to rank those alternatives (factors). Based on the result, the major factor is affiliation while the rest is course offered, cost of The most preferred is IPTS that represents a better affiliation